2012
DOI: 10.2967/jnumed.111.095786
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Mortality Assessment Improved by Evaluation of Cardiac Sympathetic Nerve Activity in Combination with Hemoglobin and Kidney Function in Chronic Heart Failure Patients

Abstract: We examined prognostic interactions among cardiac autonomic function assessed by 123 I-labeled metaiodobenzylguanidine ( 123 I-MIBG) activity, hemoglobin, and kidney function in chronic heart failure patients. Anemia, chronic kidney disease, and impairment of cardiac sympathetic function have been shown as determinants of prognosis in heart failure patients, but there has been little information on their synergistic correlations with cardiac mortality. Methods: After evaluations of hemoglobin and estimated glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
19
0
1
Order By: Relevance
“…The precise mechanisms underlying cardiac mortality have not been determined. Together with the results of our previous studies, however, it has been shown that impairment of cardiac sympathetic nerve function may exacerbate LV hypertrophy and increase LVMD in association with cardio‐renal anaemia syndrome, leading to lethal cardiac events in HF patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The precise mechanisms underlying cardiac mortality have not been determined. Together with the results of our previous studies, however, it has been shown that impairment of cardiac sympathetic nerve function may exacerbate LV hypertrophy and increase LVMD in association with cardio‐renal anaemia syndrome, leading to lethal cardiac events in HF patients.…”
Section: Discussionsupporting
confidence: 72%
“…Impaired kidney function or chronic kidney disease and anaemia are known to be closely correlated with cardiac outcomes in HF patients, independently of LV systolic function. 3,4,21,22 The precise mechanisms underlying cardiac mortality have not been determined. Together with the results of our previous studies, [21][22][23][24] however, it has been shown that impairment of cardiac sympathetic nerve function may exacerbate LV hypertrophy and increase LVMD in association with cardio-renal anaemia syndrome, 25 leading to lethal cardiac events in HF patients.…”
Section: Conventional Clinical Biomarkersmentioning
confidence: 99%
“…However, the present results cannot be used to indicate which mode of death will affect a particular high-risk patient. Sudden death per se is an outcome resulting from multifactorial pathologies and several triggers that could be modulated by interaction in various clinical conditions, including diabetic state, kidney function, and anemia (31). Hemodynamic instability enhances tachyarrhythmias via augmentations of afferent and efferent autonomic neuronal regulation and the renin-angiotensin-aldosterone system, leading to ischemia and myocyte injury, all of which in turn produce a vicious cycle resulting in pump failure and lethal arrhythmic events.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have demonstrated independent and incremental prognostic values of cardiac 123 I-MIBG imaging for patients with chronic HF in combination with clinical information, such as a history of myocardial infarction, New York Heart Association (NYHA) functional class, left ventricular ejection fraction (LVEF), plasma brain natriuretic peptide (BNP) level, and coexisting noncardiac conditions (such as diabetes mellitus, impaired kidney function, and anemia) (2,10,15,19,20,25,(34)(35)(36). The prognostic value has been shown irrespective of the etiologies (ischemic or nonischemic) of HF and LVEF (Fig.…”
Section: Incremental Clinical Benefits Of Cardiac 123 I-mibg Imaging mentioning
confidence: 99%
“…A diabetic heart is also likely to have impaired 123 I-MIBG activity (low HMR and 123 I-MIBG defect) in association with disease progression (14). Table 1 summarizes major investigations that prospectively monitored patients with chronic HF for more than 2 y with an endpoint of cardiac death (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). (26).…”
Section: Clinical Use Of 123 I-mibg Studies Leading To Japanese Nuclementioning
confidence: 99%